Experimental study on the biopolymer hydrogel effect on pile driving resistance - Kim, Mintae; Park, Suhyuk; Chang, Ilhan (Geotechnical Special Publication, 2023)
In practice, pile foundation installation is accompanied by vibration and noise. Furthermore, structural faults along the pile may emerge if the surrounding ground has greater strength and damping than expected. Due to its sufficient strengthening and low environmental impact, biopolymer-based soil treatment (BPST) has recently been recognized as a new ground improvement technology. Because most biopolymer hydrogels have a shear thinning rheology, we conducted an experiment to see whether biopolymer hydrogels could mitigate pile penetration resistance when driving piles after installation. A pile model (40 mm in diameter × 740 mm in length) capable of measuring total resistance and tip resistance simultaneously has been fabricated for laboratory experiments. A biopolymer hydrogel spraying system, which consists of a two-way nozzle near the pile-ground interface on the surface, tubing for hydrogel transport, and a precision syringe pump for flow rate-controlled injection, has been introduced in this study. The pile model was penetrated into a pluviated sand chamber (380 mm in diameter × 900 mm in depth), with and without biopolymer hydrogel spraying during pile penetration. After pile installation tests were conducted at various times to determine when the injected biopolymer hydrogels should smear into the surrounding ground and improve pile-soil interaction. As a result, it was confirmed that the resistance to penetration of the model pile was reduced by about 17%.
Keywords: Driving pile; Effect on piles; Ground improvement; Penetration resistances; Pile penetration; Shear-thinning rheology; Soil treatments; Structural faults; Tip resistance; Total resistance